Prostor jako paradigma výuky - Madro, Oskar (Vysoké učení technické v Brně. Fakulta architektury)
Bakalárska práca sa zaoberá riešením vysokoškolského areálu VUT medzi ulicami Údolní, Úvoz a Tvrdého, a návrhom novej budovy brnenskej Fakulty architektúry. Presun našej školy do kontaktu s Fakultou výtvarných umení, ktorá dnes v areáli sídli, dáva možnosť vytvoriť nie len školský areál, ale dôležitý kultúrny bod na mape mesta Brna. Koncept stojí na vnútornej analýze provozu a väzieb fakulty, ktoré sú transformované do schémy átria.

The bachelor thesis is seeking for an answer about the future of BUT university area between the streets Úvoz, Údolní and Tvrdého, and about the design of new faculty of architecture. The idea of connecting our school with Faculty of fine arts, which is already situated in the area, gives the opportunity to not only create school complex, but to aim for a new cultural spot of the city of Brno. The concept is built uppon the analysis of the working of faculty and its inner connections, that are transformed into the scheme of atrium.
Teaching-space paradigm
Keywords: škola; atrium; betón; school; atrium; concrete